2021
DOI: 10.1101/2021.03.04.21252945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The COVIDome Explorer Researcher Portal

Abstract: COVID-19 pathology involves dysregulation of diverse molecular, cellular, and physiological processes. In order to expedite integrated and collaborative COVID-19 research, we completed multi-omics analysis of hospitalized COVID-19 patients including matched analysis of the whole blood transcriptome, plasma proteomics with two complementary platforms, cytokine profiling, plasma and red blood cell metabolomics, deep immune cell phenotyping by mass cytometry, and clinical data annotation. We refer to this multidi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For the analysis of the miR-2392 targets in the blood tissue, we downloaded whole blood transcriptome data and plasma proteome data from The COVIDome Explorer Researcher Portal (Sullivan et al, 2021). For Transcriptome data we used the following filters: Category ''Effect of COVID-19 status,'' Platform ''Blood,'' Statistical test ''Student's t-test,'' Adjustment method ''none,'' Sex ''male'' and ''female,'' Age Group ''All.''…”
Section: Star+methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the analysis of the miR-2392 targets in the blood tissue, we downloaded whole blood transcriptome data and plasma proteome data from The COVIDome Explorer Researcher Portal (Sullivan et al, 2021). For Transcriptome data we used the following filters: Category ''Effect of COVID-19 status,'' Platform ''Blood,'' Statistical test ''Student's t-test,'' Adjustment method ''none,'' Sex ''male'' and ''female,'' Age Group ''All.''…”
Section: Star+methodsmentioning
confidence: 99%
“…Proteomic and transcriptomic analysis in blood from COVID-19 patients using COVIDome (Sullivan et al, 2021) revealed interesting patterns between RNA and protein levels for miR-2392 targets from miRmap, ClueGO,miRwalk,miRnet,and miRDB (Figures 3J and 3K). Several miR-2392 targets in tissue show a significant transcriptional increase in COVID-19-positive samples, with small to no changes on the proteomics level: PLK1, CD38, PYCR1, RNASE1, BIRC5, RRM2, and SIGLEC1 (Figure 3J).…”
Section: Mir-2392 Targets Mitochondrial and Inflammatory Pathways Associated With Sars-cov-2mentioning
confidence: 99%
“…In this study, we analyzed the multi-omics datasets generated by the COVIDome Project (covidome.org) to investigate IFN signaling in hospitalized COVID19 patients. The COVIDome Project datasets have been previously described (16,17) and include matched analysis of whole blood transcriptome, plasma proteomics via complementary SOMAscan ® assays and mass spectrometry, measurement of 82 immune factors by multiplexed immunoassays, SARS-CoV-2 seroconversion assays, immune cell profiling by mass cytometry, plasma and red blood cell metabolomics, as well as annotated clinical data. The COVIDome Project cohort analyzed in this study consists of 73 hospitalized COVID19 patients with mild-to-moderate disease versus 32 controls (see Supplementary file 1 for cohort characteristics and Methods).…”
Section: Variable Ifn Signaling In Covid19 Associates With Levels Of a Specific Subset Of Ifn Ligandsmentioning
confidence: 99%
“…In sum, our analyses and datasets provide a rich resource to advance understanding of the IFN ligand family in humans. In order to accelerate the use of these datasets at a global scale, they are made readily available through the COVIDome Explorer Researcher Portal (covidome.org) (17), where users can rapidly recreate the cross-omics correlations described here, investigate any other cross-omics correlations of choice, and download all data for further analysis. Blood processing.…”
Section: Supplement 1f-g)mentioning
confidence: 99%
See 1 more Smart Citation